Edukasi Awal Koperasi dalam Mendukung Pemberdayaan Desa - Sarah Haryani; Putri Mulyanti; Adhitya Almanfaluthi Pradigda; Fauziah Afriyani; Lili Syafitri (Jurnal Pengabdian Masyarakat Waradin, 2025)
A cooperative is an economic institution founded on the principles of solidarity and mutual cooperation with the primary objective of improving the welfare of its members. However, low cooperative literacy, particularly in rural areas, remains a major obstacle in optimizing the role of cooperatives as community-based economic institutions. In response to this challenge, a Community Service Program (Kuliah Kerja Nyata/KKN) was conducted in Pulau Harapan Village to provide fundamental knowledge about cooperatives and foster residents’ interest in establishing a community-driven economic organization. The program was implemented in late July 2025 using a participatory approach through three stages: material preparation, interactive socialization with membership and savings-loan simulations, and activity evaluation. A total of 62 participants—including village officials, women farmer groups, MSME actors, and local traders—were actively involved in the program. The results of the activities indicated a significant improvement in participants’ understanding of cooperative benefits. This was reflected in their enthusiastic engagement during discussions as well as the emergence of community initiatives to establish a village cooperative. As a follow-up, plans for an official founding meeting and continuous mentoring have been scheduled. Through these efforts, the cooperative is expected to grow into a sustainable pillar of the local economy